A Year in the Life of a Third Space Urban Teacher Residency - Taylor, Monica. author. aut Link
X, 304 p.
Keywords: This book weaves together voices of faculty, residents, mentors, administrators, community organizers, and students who have lived together in a third space urban teacher residency program in Newark as they reinvent math and science teaching and teacher education through the lens of inquiry. Each chapter includes narratives from multiple perspectives as well as tools we have used within the program to support and build change, providing readers with both real cases of how an urban teacher residency can impact school systems, and concrete tools and examples to help the reader understand and replicate aspects of the process. Capturing both the successes but also the tensions and challenges, we offer a kaleidoscopic view of the rich, complex, and multi-layered ways in which multiple stakeholders work together to make enduring educational change in urban schools. Our third space NMUTR has been a fragile utopian enterprise, one that has relied on a shared commitment of all involved, and a deep sense of hope that working collaboratively has the potential, even if not perfect, to make a difference.